Emergence of microbial resistance against nanoparticles: Mechanisms and strategies - Kamat, Siya; Kumari, Madhuree (Frontiers in Microbiology, 2023)
Antimicrobial nanoparticles have gained the status of a new generation of drugs that can kill bacterial pathogens by multiple means; however, nanoparticle resistance acquired by some bacterial pathogens has evoked a cause of concern. Several reports suggested that bacteria can develop nanoparticles, specifically metal nanoparticle resistance, by mechanisms: nanoparticle transformation-induced oxidative stress, membrane alterations, reversible adaptive resistance, irreversible modifications to cell division, and a change in bacterial motility and resistance. Surface properties, concentration and aggregation of nanoparticles, biofilm forming and metal exclusion capacity, and R plasmid and flagellin synthesis by bacteria are crucial factors in the development of nanoparticle resistance in bacteria. Studies reported the resistance reversal by modifying the surface corona of nanoparticles or inhibiting flagellin production by bacterial pathogens. Furthermore, strict regulation regarding the use and disposal of nano-waste across the globe, the firm knowledge of microbe–nanoparticle interaction, and the regulated disposal of nanoparticles in soil and water is required to prevent microbes from developing nanoparticle resistance.